Development of bronchial mucous plugs under anesthesia and removal by bronchoscopy during open-heart surgery - Yenmez, Kamil; Sarıoğlu, Tayyar (The Turkish Journal of Pediatrics, 1988)
A seven-year-old girl who developed total left pulmonary atelectasis as a result of left main bronchial obstruction by a mucous plug during repair of an atrial septal defect is presented. Before discontinuing the cardiopulmonary bypass (CPB) procedure, attempts were made to expand the left lung, but failed. Continued full-flow of CPB made it possible to perform a bronchoscopy. The airway was cleared, thereby completely re-expanding the left lung for adequate ventilation. Thereafter, the CPB procedure was gradually discontinued and the surgery was completed successfully. In conclusion, performing a bronchoscopy facilitated by continued full-flow of CPB should be considered an absolutely safe method in dealing with these kinds of complications which can occur during open-heart surgery.